Localized interfacial activation effect within interconnected porous photothermal matrix to promote solar-driven water evaporation. Issue 19 (14th April 2022) - Zhang, Jingjing; Ma, Jiaxiang; Liu, Dongmei; Liu, Dongqing; Han, Yu; Xu, Ying; Cui, Fuyi; Wang, Wei
Abstract : A localized interfacial activation strategy for enhancing solar evaporation is proposed via an interconnected porous photothermal matrix weakening the vaporization enthalpy of interfacial water molecules by its localized amphiphilic micro-skeleton. Abstract : Herein, a localized interfacial activation strategy is proposed to promote solar evaporation. Considering that surfactants can weaken water interaction but on the other hand block evaporation due to physical coverage, surfactant-like graphene oxide (GO) and polydopamine (PDA) are assembled to be an interconnected porous photothermal matrix (IPPM) via an acid-assembly method. Hence, the activation interface is physically localized at the micro-frame surface of IPPM (composed of an rGO frame and PDA with an outward-facing indole structure), which can effectively decrease the interaction energy of interfacial water molecules. Meanwhile, the interconnected water channels in the IPPM ensure adequate water supplementation for interfacial evaporation. Consequently, the IPPM not only displays a high performance of 2.2 kg m −2 h −1 under 1 sun irradiation, but in particular exhibits an unparalleled advantage with a flux of over 10 kg m −2 h −1 under concentrated irradiation below 5 sun. The present development takes a new step towards the practical application of solar evaporation in the future.